LUTEAL DEFICIENCY: AN IMPORTANT CAUSE OF CONCEPTION FAILURE IN SAHIWAL CATTLE - AYAM, V B S; AWASTHI, M K; KHAN, J R; POYAM, M R (The Indian Journal of Animal Reproduction, 2016)
Plasma progesterone was determined during mid-luteal phase to evaluate the impact on subsequent conception in Sahiwal cattle (n=40) that were subjected to artificial insemination (AI) with good quality frozen semen about 12 h after the onset of estrus. Blood plasma was collected on day 10 post-AI and progesterone was determined through ELISA. Pregnancy diagnosis between days 50-60 post-AI divided the animals into conceived and non-conceived group (n=20 each). In both groups, plasma progesterone was similar (6.38±0.63 vs. 4.61±0.76 ng/ml, p>0.05). However, in non-conceived group, five animals had plasma progesterone 5.0 ng/ml on day 10 post-AI conceived. Thus, an adequate progesterone release during early stages of conception may have a role in subsequent pregnancy maintenance.
Keywords: Luteal deficiency; Mid-luteal phase; Pregnancy; Progesterone; Sahiwal cattle